Effect of the ethanolic extract of Erythroxylum novogranatense var. truxillense and Erythroxylum coca var. coca front to Streptococcus mutans. - Salcedo Calderón, María Del Rosario (2022)
Objectives: To compare the antibacterial effect of the ethanolic extracts of two varieties of coca leaf “in vitro”: Erythroxylum coca var. coca and Erythroxylum novogranatense var. truxillense on Streptococcus mutans. Material and methods: Using the method of diffusion by discs, the ethanolic extracts of the two varieties were applied at concentrations 100%, 50%, 25% and 12.5% with positive controls of Chlorhexidine 0.12% and negative of 96º Alcohol in the cultures of the Streptococcus mutans strain (ATCC 25175) sown in Tripticasa Soya Agar. Incubation was performed at 37 ° C for 48 hours under conditions of partial anaerobiosis. The statistical analysis was carried out with the SPSS Version 22 program by means of the Mann Whitney U Test and Kruskal Wallis. Results: Erythroxylum coca var. coca 100% and 50% had a greater inhibition halo 18.65 ± 2.434 and 17.10 ± 2.654 with respect to the ethanolic extract of Erythroxylum novogranatense var. truxillense that were 15.30 ± 1.895 and 14.05 ±1.932. respectively. Conclusions: It was determined that the ethanolic extract of Erythroxylum coca var. coca 100% and 50% has a greater antibacterial effect than the Erythroxylum novogranatense var. truxillense 100% against Streptococcus mutans.